Teasing Apart Impacts of Human Activity and Regional Drought on Madagascar’s Large Vertebrate Fauna: Insights From New Excavations at Tsimanampesotse and Antsirafaly - Godfrey, Laurie R.; Crowley, Brooke E.; Muldoon, Kathleen M.; Burns, Stephen J.; Scroxton, Nick; Klukkert, Zachary S.; Ranivoharimanana, Lovasoa; Alumbaugh, Jamie; Borths, Matthew; Dart, Ryan; Faina, Peterson; Goodman, Steven M.; et al. (Frontiers in Ecology and Evolution, 2021)
Madagascar experienced a major faunal turnover near the end of the first millennium CE that particularly affected terrestrial, large-bodied vertebrate species. Teasing apart the relative impacts of people and climate on this event requires a focus on regional records with good chronological control. These records may document coeval changes in rainfall, faunal composition, and human activities. Here we present new paleontological and paleoclimatological data from southwestern Madagascar, the driest part of the island today. We collected over 1500 subfossil bones from deposits at a coastal site called Antsirafaly and from both flooded and dry cave deposits at Tsimanampesotse National Park (TNP). We built a chronology of Late Holocene changes in faunal assemblages based on 65 dated specimens and subfossil associations. We collected stalagmites primarily within TNP but also at two additional locations in southern Madagascar. These provided information regarding hydroclimate variability over the past 120,000 years. Prior research has supported a primary role for drought (rather than humans) in triggering faunal turnover at Tsimanampesotse. This is based on evidence of: (1) a large freshwater ecosystem west of what is now the hypersaline Lake Tsimanampesotse, which supported freshwater mollusks and waterfowl (including animals that could not survive on resources offered by the hypersaline lake today); (2) abundant now-extinct terrestrial vertebrates; (3) regional decline or disappearance of certain tree species; and (4) scant local human presence. Our new data allow us to document the hydroclimate of the subarid southwest during the Holocene as well as shifts in faunal composition (including local extirpations, large-vertebrate collapse, and the appearance of introduced species). These records affirm that climate alone cannot have produced the observed vertebrate turnover in the southwest. Human activity, including the introduction of cattle as well as associated changes in habitat exploitation, also played an important role.